Enhancing the Thermal and Mechanical Properties of Organic-Inorganic Hybrid Nanocomposite Films Based on Poly Lactic Acid/OMMT Nano Clay - Selvan, S. Mahendra; Duraibabu, D.; Gnanaprakasam, A.; Kumar, S. Ananda (Journal of Coating Science and Technology, 2019)
Organic (PLA) inorganic (OMMT nano clay) hybrid nanocomposite films were fabricated using poly lactic acid (PLA) with various weight percentages (1-3wt%) of organically modified montmorillonite (OMMT) nano clay by means of one step solvent casting method. The thermal, mechanical and water absorption properties were determined as per standard testing methods to determine the optimum percentage loading of OMMT nano clay within the PLA-OMMT nanocomposite was investigated. The surface morphology of the organic-inorganic hybrid nanocomposite films was analyzed through XRD, SEM, and TEM surface analytical techniques. The incorporation of OMMT clay in to PLA matrix is found to have enhanced the thermo-mechanical properties. The water absorption and solubility test results also support the data from thermo-mechanical tests. The 2 wt % OMMT clay loaded PLA films showed the best results among all. The obtained results showed that the thermal, mechanical and water absorption properties could be increased significantly with the optimum incorporation of OMMT nano clay in a PLA matrix, in comparision wih the neat PLA.